Influence of Environmentally Eco-Friendly Pozzolanic Materials on Microstructures and Durability of Environmentally-Friendly High-Strength Concrete - Mohamed Amin, Khaled Abu el-hassan, Omar Mohamed Omar Ibrahim,Ahmed Mohamed Nasr (Design Engineering, 2021)
Cement is a popular material in construction all over the world but Carbon dioxide emission is the largest atmospheric pollutant of cement. Therefore, researchers must develop new materials, such as an alternative to cement such as supplementary cementitious materials, SCM. The paper aims to investigates the effects of of metakaolin (Mk), silica fume (SF) and fly ash (FA) on properties and durability of high strength concrete (HSC). The studies of fresh and hardened properties are slump, air content, compressive strength, splitting tensile strength, flexural strength, bond strength, modulus of elasticity and permeability. Also, the research investigates the effect of elevated temperature degree (22, 100, 300, 500 and 700 °C) for an exposure period equals 2 hours on the concrete compressive and flexural strength. While, the chloride attack at 28 ,90 and 150 days on the compressive strength of concrete mixes with different concentration of sodium chloride at 5, 25 and 50 gm/liter of water. At this experimental works, cement is replaced by (0%, 5%, 10%, 15% and 20%) from metakaolin or silica fume or fly ash by weight of used cement. The content of cementitious materials in all mixes was used 500Kg/m3and the water/binder materials ratio (w/b) equal 0.3. Performances of metakaolin mixes were compared with control mix, silica fume mixes and fly ash mixes. Mk concrete mixes showed a better consistency than other mixes of experimental program. The compressive strength and other hardened properties of concrete with Mk were higher than that of reference concrete. The test results showed that a FA content or SF content of about 15% by replacement of cement gave concrete with the optimum strengths. The test results showed that a Mk content of about 10% by replacement of cement gave concrete with the optimum strengths. As the replacement levels was increased, the mechanical properties of the silica fume concrete increased at all ages similarly to that of the metakaolin and fly ash concrete. The enhancement in the compressive strength at age 28 days were (11.6, 27.6, 24.7, and 22.6% ), (16.8, 25.0, 33.5, and 27.6% ), and (8.7, 16.1, 25.2, and 19.9% ) when using Mk, SF, and FA as a replacement with (5, 10, 15, and 20% ) respectively. The results showed that using Mk in concrete mixes increased the residual compressive and flexural strength after exposure to elevated temperatures than mixes containing SF or FA. The results showed that the replacement materials to all mixes improves the performance of the produced blended concrete when exposed to elevated temperatures up to 100 oC. SF concrete mixes showed a better compressive strength after immersion in sodium chloride solution at 28, 90 and 150 days than Mk, FA and control concrete mixes.